Pengaruh Laju Pengadukan Terhadap Biokonversi Reject Nanas Menjadi Bioetanol - Intan Oktaviani; Adrianto Ahmad; Chairul Chairul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Bioethanol production can be done by a process of fermentation material containing glucose, cellulose fiber and starch. Pineapple is one of the ingredients containing glucose. This study produces bioethanol from reject pineapple juice. The purpose of this study to determine the effect of stirring rate on bioethanol yield and to get the best conditions in the manufacture of bioethanol made from pineapple juice reject. There are several stages in the research, the preparation of raw materials, fermentation, and purification products. The variables used are the stirring speed in the process of fermentation: 100, 150, 200, 250, and 300 rpm with fermentation time 12, 24, 36, 48, 72, 84, 96, 108 and 120 hours. Anaerobic fermentation process takes place with the help of the yeast Saccharomyces cerevisiae with the addition of some nutrients. To measure the ethanol formed, the purification process is carried out using a rotary evaporator. The results showed that the highest ethanol content of 10% v/v with yield of 95.32% obtained at the stirring rate of 200 rpm with a fermentation time of 60 hours.Keywords: Bioethanol, Reject pineapple, Stirring, Saccharomyces cerevisiae.